2000
DOI: 10.1021/es990726z
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent for Eliciting Environmental Values

Abstract: Agreeing to participate in a study eliciting environmental values means agreeing to abide by the commitment implied by any proposal that one accepts or rejects in it. That might mean anything from addressing the gist of an issue to expressing an explicit willingness to pay for an environmental change. By soliciting such participation, investigators promise to provide the information that participants need in order to evaluate the proposals being presented. This paper proposes a standard for providing such info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…We are likely to be much more effective if we focus our attention on identifying value differences and designing processes that allow articulation of and reflection on values in the light of decisions that must be taken. Decision sciences provide many helpful tools that allow individuals and groups to clarify their values, and there is some evidence that reflection about and articulation of value positions can reduce conflict and allow for a more effective search for compromises (98)(99)(100)(101).…”
Section: Lessons For Science Communicationmentioning
confidence: 99%
“…We are likely to be much more effective if we focus our attention on identifying value differences and designing processes that allow articulation of and reflection on values in the light of decisions that must be taken. Decision sciences provide many helpful tools that allow individuals and groups to clarify their values, and there is some evidence that reflection about and articulation of value positions can reduce conflict and allow for a more effective search for compromises (98)(99)(100)(101).…”
Section: Lessons For Science Communicationmentioning
confidence: 99%
“…The literature on risk perception and communication suggests that there are a number of reasons why health warnings are often not heeded or acted upon by the public [20]. These include message features (ambiguity of risk information or the actions needed to overcome risk), poor communicator abilities, personal characteristics of the audience (prior experiences, personality traits, cognitive biases, attitudes toward personal vulnerability, distrust of authorities), and social influences through the media and informal social networks [20][21][22]. In particular, [23,24] has consistently demonstrated that there are many factors that influence the perception of risk-among them, the salience of risk issues, the information provided by the mass media and the way in which they are presented.…”
Section: Theoretical Model About Attitudes and Behavioursmentioning
confidence: 99%
“…Researchers have an obligation to provide respondents with the conditions needed to produce the valuations they seek [Fischhoff (2000)]. Otherwise, they (and those who use their work) may misrepresent respondents.…”
Section: A Cognitive Approach To Eliciting Stated Preferences For Envmentioning
confidence: 99%
“…With gist studies, the primary risk is asking respondents to reflect too hard on their values, taking them beyond their initial gut reactions, perhaps even throwing them into question [Fischhoff (1991[Fischhoff ( , 2000, Wilson et al (1993)]. …”
Section: A Cognitive Approach To Eliciting Stated Preferences For Envmentioning
confidence: 99%
See 1 more Smart Citation